Quality of life after curative liver resection: a single center analysis - Bruns, Helge; Krätschmer, Kirsten; Hinz, Ulf; Brechtel, Anette; Keller, Monika; Büchler, Markus W.; Schemmer, Peter (World journal of gastroenterology, 2010)
Quality of life after curative liver resection: A single center analysis